Anomalies in the Distribution Patterns of Rainfall in Dharwar District, Karnataka - Nayak, L.T. (National Geographical Journal of India, 2022)
Rainfall and soil are the two important natural elements which play a vital role in agriculture production and existence of living organisms. The occurrence and distribution of rainfall over a region depends on various features, some of them are natural such as topography, water bodies, distance from the sea, temperature etc. These features affect differently the seasonal rhythms of the air circulation and also the rainfall distribution. The present study attempts to assess the spatio-temporal distribution of rainfall, rainfall variability and stability, abnormality of rainfall in Dharwad district, Karnataka. The present study is based on secondary data and analysis has been made at 14 raingauge stations for 10 years from 1999 to 2008. In this process mean monthly, annual and mean seasonal rainfall have been computed. The paper also describes rainfall characteristics in denoted rainfall regions namely semimalnad region, central region, and eastern region. The high amount of rainfall and number of rainy days are recorded more in semi-malnad region and remaining two rainfall regions recorded marginal rainfall.